Exploring the power of spectrophotometric technique in determination of oxytetracycline and lidocaine in their pharmaceutical dosage form as well as in the presence of toxic lidocaine impurity: univariate versus multivariate analysis - Naglaa Ahmed; Ahmed Hemdan; Hala ZaaZaa; Maha Galal (BMC Chemistry)
Abstract Lidocaine poses challenges when it comes to direct spectrophotometric measurement due to the lack of sharp peak within its spectra in zero-order. This lack of a distinct peak makes it difficult to accurately quantify lidocaine using traditional direct spectrophotometric methods. In our study, different univariate and multivariate spectrophotometric techniques have been established and their validity has been assessed for the determination of the mixture of Lidocaine HCl (LD), Oxytetracycline HCl (OTC) together with LD carcinogenic impurity [2,6- dimethylaniline] DMA. LD was resolved from the other two components using ratio difference and derivative ratio methods. OTC was determined in zero- order at 360 nm and by using constant value and concentration value methods, while DMA was determined by using constant multiplication at 237 nm as well as by using constant value and concentration value methods after elimination of OTC by ratio subtraction technique. Moreover, Partial Least Squares and Principal Component Regression multivariate approaches were applied to quantify and evaluate the mixture. The developed methods underwent validation following International Council for Harmonization guidelines. The validation process demonstrated that all suggested methods are accurate and selective in their measurements. Additionally, statistical analysis was conducted to compare the developed and reported methods. Furthermore, one-way analysis of variance was performed to compare both proposed and reported spectrophotometric methods.